Atopic condition of the esophagus - eosinophilic esophagitis - literature review - Pastuszka, Artur; Serwońska, Karolina; Galanty-Ochyra, Aleksandra; Węgrzyn, Jan; Czarnecki, Adam; Jabłońska, Olga; Zając, Piotr; Fijałkowski, Łukasz; Nosal, Aleksandra (Journal of Education, Health and Sport, 2025)
Introduction and purpose Eosinophilic esophagitis (EoE) is a chronic, immune-mediated disorder causing esophageal dysfunction in children and adults. Characterized by eosinophilic inflammation, EoE leads to dysphagia, food impaction, and esophageal remodeling. Since its classification in the 1990s, research has expanded, yet aspects of its pathogenesis, diagnosis, and management remain under investigation. This review compiles current knowledge on EoE, covering its pathophysiology, epidemiology, clinical presentation, diagnosis, treatment, and prognosis. By integrating recent findings and guidelines, it aims to enhance understanding and optimize care. Description of the state of knowledge EoE is defined by eosinophilic infiltration of the esophageal mucosa, leading to dysfunction. Diagnosis relies on histologic criteria, with ≥15 eosinophils per high-power field in biopsies. Endoscopic tools like the EoE Endoscopic Reference Score (EREFS) aid evaluation, though differentiation from GERD remains challenging. Treatment includes dietary modifications, pharmacologic therapy, and endoscopic interventions. First-line options are dietary elimination, proton pump inhibitors (PPIs), and topical corticosteroids, while emerging biologics target inflammatory pathways. Endoscopic dilation is reserved for fibrostenotic cases. Despite therapeutic advancements, EoE is a chronic condition requiring long-term management. Continued research is needed to refine treatment strategies and improve outcomes. Conclusions EoE requires lifelong management. While dietary, pharmacologic, and endoscopic treatments control symptoms, they do not halt disease progression. Biologic therapies offer promising advances, but further studies are needed to optimize long-term strategies and patient care.